Estructuras anulares en la cordillera oriental de colombia y su relación a fenómenos diapíricos (1995)
There is a wide area, in the Cordillera Oriental of Colombia, which presents very specialgeographic and geologic characteristics. In the same zone there are some very well defined types of mineralization, which do not appear in the rest of the country.  The tectonics of the zone presents not well explained particularities. The zone extends from Villarrica (Tolima) (southern part) to Mesa de Los Santos and Sierra del Cocuy piedmont (north); and from the Borde Llanero fault to the east, to Bituima and Salina faults to the west.